Pengaruh Penggunaan Aplikasi Quizizz Dan Perhatian Orangtua Terhadap Motivasi Belajar PAK Siswa Kelas XI SMA Negeri 1 Bangko Pusako Tahun Pembelajaran 2023/2024 - Dessy Kristina Sagala; Albiner Siagian; Johari Manik; Hisardo Sitorus; Betty A.S Pakpahan (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine: 1) the magnitude of the influence of using the Quizizz application on student learning motivation; 2) the great influence of parental attention on student learning motivation; 3) the big influence of using the quizizz application and parental attention together on student learning motivation. The method used in this research is a quantitative research method. The population was all 250 students of class Data was collected using a closed questionnaire with 56 items. The results of data analysis show that: 1) the calculated F value > F table between the principal's Innovative leadership on Teacher Work Motivation is 17.954 > 3.15, thus it is known that there is an influence between the principal's Innovative leadership on the Work Motivation of Public High School Teachers in SMA Negeri 1 Bangko Pusako is 25.7%, 2) the calculated F value > F table between the use of the Quizizz application and parental attention to student learning motivation, namely 27.811 > 3.15, thus it is known that there is an influence between the use of the Quizizz application and parental attention to learning motivation. Bangko Pusako 1 Public High School students are 34.8%, 3) the calculated F value > F table influences the use of the Quizizz application and parental attention on student learning motivation, namely 16.654 > 3.15, thus it is known that there is use of the Quizizz application and parental attention. Regarding the Learning Motivation of Bangko Pusako 1 Public High School Students, it is 39.5%, thus Ha is accepted and H0 is rejected.